The impact of macroeconomic determinants on the banking sector development in Nepal - Gwachha, Krishna Prasad (The International Research Journal of Management Science, 2022)
Abstract Background: The concept of banking sector development is multi-dimensional, and it is difficult to establish a single description for it because it is an interconnected process that encompasses increases in the number and quality of financial services. Objectives: The objective of the study is to examine the impact of macroeconomic determinants on banking sector development in Nepal. Methods: The study applied the vector error correction model (VECM) approach technique with economic time series data ranging from 1995 to 2020. The study employed the VECM model to avoid the spurious regression problem in the construction of contemporary time series econometrics. The co-integration analysis is used in the study to determine the long-run equilibrium relationship between the macroeconomic variable and the banking sector development of the model. Banking sector development is measured by the arithmetic average of the normalized values of banking depth, banking efficiency, and banking stability. Result: This study reveals that per capita GDP and remittances have a positive and significant impact on the banking sector development. Similarly, government expenditure and stock market capitalization have positive and statistically significant roles to explain banking sector development in Nepal. In addition, it demonstrates that trade openness and inflation have a marginally negative but insignificant impact on banking sector development. Conclusion: There is a long-term equilibrium relationship between macroeconomic variables and banking sector development. Macroeconomic policies and institutional quality play an important role in the banking sector development. Implications: For policymakers since it clarifies the significance of sound macroeconomic policies in the development of the banking industry while taking into account the quality of the existing institutional infrastructure.